Intra and inter observer agreement in the mobility assessment of the upper thoracic costovertebral joints. - Cibulka, Michael; Buck, Justin; Busta, Bria; Neil, Erika; Smith, Drake; Triller, Reece (Physiotherapy Theory & Practice, 2023)
Determining the mobility of the costovertebral joints might be important in patients with neck-upper thoracic pain. Little research has been performed on observer agreement when assessing the mobility of these joints. The purpose of this study was to determine intra- and inter-observer agreements when assessing costovertebral joint mobility of the upper three ribs in those with and without neck pain and to compare the difference between the Kappa and AC statistic. Forty-four participants, with and without current neck/upper-thoracic pain, were assessed by two raters. Raters applied a posterior to anterior pressure to the anatomical neck of the first three ribs bilaterally. Mobility was graded: normal, increased, or decreased. An AC1, for nominal data, AC2 for ordinal data, and the Kappa statistics were used to analyze the results. The AC statistics determines chance agreement different than Kappa. AC1 showed "moderate to very good" (0.74–1.0) intra-rater reliability, while inter-rater reliability showed "fair to good" agreement (0.51–0.79). Using the AC2 Intra-rater reliability was "very good" and "almost perfect" (AC2: 0.93–1.0), while using the AC2 was "good to very good" and "good to almost perfect" (0.76–0.94). Kappa values for intra-rater reliability ranged from "fair to moderate" (0.38–0.54), while inter-rater reliability ranged from "poor to fair" (−0.10–0.26). Posterior/anterior pressure is a reliable method to assess the mobility of the upper costovertebral joints. Assessing costovertebral mobility is important when establishing a movement diagnosis in patients with neck/upper thoracic pain.